Healthcare Professionals' Own Experiences of Domestic Violence and Abuse: A Meta-Analysis of Prevalence and Systematic Review of Risk Markers and Consequences. (July 2023) - Dheensa, Sandi; McLindon, Elizabeth; Spencer, Chelsea; Pereira, Stephanie; Shrestha, Satya; Emsley, Elizabeth; Gregory, Alison
Background: Globally, healthcare professionals (HCPs) are increasingly asked to identify and respond to domestic violence and abuse (DVA) among patients. However, their own experiences of DVA have been largely ignored. Aim: To determine the prevalence of current and lifetime DVA victimisation among HCPs globally, and identify risk markers, consequences and support-seeking for DVA. Method: PubMed, EMBASE, PsycINFO, CINAHL ASSIA and ProQuest were searched. Studies about HCPs' personal experience of any type of DVA from any health service/country were included. Meta-analysis and narrative synthesis were adopted. Results: Fifty-one reports were included. Pooled lifetime prevalence was 31.3% (95% CI [24.7%, 38.7%] p < .001)) and past-year prevalence was 10.4% (95% CI [5.8%, 17.9%] p <.001). Pooled lifetime prevalence significantly differed (Qb=6.96, p < .01) between men (14.8%) and women (41.8%), and between HCPs in low-middle income (64.0%) and high-income countries (20.7%) (Qb = 31.41, p <.001). Risk markers were similar to those in the general population, but aspects of the HCP role posed additional and unique risks/vulnerabilities. Direct and indirect consequences of DVA meant HCP-survivors were less able to work to their best ability. While HCP-survivors were more likely than other HCPs to identify and respond to DVA among patients, doing so could be distressing. HCP-survivors faced unique barriers to seeking support. Being unable to access support – which is crucial for leaving or ending relationships with abusive people – leaves HCP-survivors entrapped. Conclusion: Specialised DVA interventions for HCPs are urgently needed, with adaptations for different groups and country settings. Future research should focus on developing interventions with HCP-survivors.